La acción como principio comprensivo - Passos, Mateus Yuri; Osorio Vargas, Raúl (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
In this short essay we firstly review the double character of comprehension as a method as an epistemological and intersubjective approach in order to present then a second pair of aspects: thinking and acting in a comprehensive perspective. In this sense, we discuss action as a key principle for comprehension as method, based on the assumption that it constitutes a second face of the comprehensive thought which is complents the first in an integrative gesture between the world of thought and the living world. As examples of comprehensive act we present the seventeen essays which constitute the “Acting with the sign of comprehension” dossier, published in this issue of the special Folios journal (n. 40, Jul./Dec. 2018), in which we are able to identify the integrality of observation, analysis and actual practice of a comprehensive thought manifested in the realms of action.